WEBSITE IMPLEMENTATION FOR MAKING SCHOLARSHIP ACCEPTANCE DECISIONS AT SMK N 1 TALANGPADANG USING THE ANALYTICAL HIEARARCHY PROCESS METHOD - Rima Mawarni; Meri Parida (IJISCS (International Journal of Information System and Computer Science), 2019)
Processing of scholarship data in SMK 1 Talangpadang generally still uses Microsoft Excel, while for data processing takes a long time. The problem that often arises is the scattering of the file for distributing scholarship receipts every year. This scholarship consists of Academic Achievement, Nonacademic Achievement, Personality, Mileage, Report Card, Organizations, Dependent Parents, Parent's Income, and Parent's Status. The method used in this study is the Analytical Hierarchy Process can also help in determining several criteria by using a different analysis from each of the specified sources.